The nonlinear convolutional equations solvable in closed form - Kakichev, V. A. (Mathematical Modelling and Analysis, 1997)
“The nonlinear convolutional equations solvable in closed form”Mathematical Modelling Analysis, 2(1), p. 75-78.First Published Online: 14 Oct 2010